Molecular Toxicology of Organophosphate Poisoning - Fery Setiawan; Arif Rahman Nurdianto; Heribertus Agustinus B Tena; Ahmad Yudianto; Jenny Sunariani; Achmad Basori; Acrivida Mega Charisma (Universitas Wijaya Kusuma Surabaya, 2022)
The use of organophosphates (pesticides and other compounds to eradicate pests), currently, to increase the fulfillment of the population's consumption needs has a double-edged sword effect, on the one hand it can increase the need for food to be consumed by the population. The negative effect that can arise is the safety of organophosphate drugs which can contaminate the soil and water sources around the place where organophosphate drugs are used. The negative effects of organophosphates are associated with the effects of xenobiotics on humans who consume them. Xenobiotics are associated with toxicdynamic effects where organophosphates cause irreversible inhibition of the enzyme acetylcholinesterase (ACh). ACh is one of the main enzymes in the nervous system that terminates impulse conduction through the hydrolysis process of acetylcholine enzymes. Acetylcholinesterase is a specific molecular target of organophosphate pesticides. The inhibition of the Ach enzyme causes the inhibition of the acetylcholine enzyme which is normally always hydrolyzed by the Ach enzyme and is a specific biological marker of pesticide poisoning. Inhibition of ACh will cause the accumulation of the enzyme acetylcholine, resulting in negative effects of organophosphate poisoning which can lead to death. In this paper, the authors collect from various sources related to the study of molecular toxicology toxidynamic effects of drug safety and organophosphate poisoning. The results of this review article show that organophosphate poisoning is associated with irreversible inhibition of the acetylcholinesterase enzyme which results in death in the individual concerned.